Can China's water rights trading system promote water resources technological innovation? - Dawei Gao; Yan Deng; Shuang Gao; Chuangbin Chen (Desalination and Water Treatment)
Water is an important resource that supports economic development and ecological security, and water pollution and water shortage pose a major threat to human survival. Therefore, improving the utilization of water resources and establishing a water rights trading system (WRTS) have become urgent tasks for achieving the goal of sustainable socio-economic development. Water resources technology innovation (WRTI) is an important driver of accelerating the construction of ecological civilization in China. In view of this, it is worth exploring whether a WRTS, as a market-based environmental policy targeting water conservation and water use efficiency, can promote WRTI within the framework of China's national policy of resource conservation and environmental protection. To address this question, this innovative study employs a quasi-natural experiment based on the WRTS implemented in China in 2014. The study selects panel data from 30 Chinese provinces (excluding Tibet, Hong Kong, Macau, and Taiwan) spanning the period from 2010 to 2020. It empirically examines the effect of the WRTS on WRTI using the difference-in-differences method. The results of the study show that the WRTS significantly increases the level of WRTI in the pilot region. In addition, the study explores the heterogeneity of WRTI across innovation types and administrative levels within the WRTS pilot districts. The results show that the WRTS is effective in stimulating the growth of WRTI. In addition, national-level pilot districts contribute more significantly to WRTI than provincial-level pilot districts. Overall, these findings provide valuable insights into the role of a WRTS in promoting the optimal allocation of water resources and its combined contribution to water conservation and protection.